Comparison of the results of the 15-meter sprint swimming (TT-15) with the results of the hundred-meter race for professional swimmers: potential and limits of applicability of the assessment at short distance - Zaitsev V.S.; Molina I. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The present study focuses on analyzing the correlation between the results of the TT-15 test (the speed of overcoming 15 meters after pushing off the wall) and the time shown by high-class swimmers when swimming 100 meters crawl in a short 25-meter pool. TT-15 is a method of measuring the time it takes for an athlete to cover a 15-meter distance after completing a turn. The initial hypothesis was that the use of TT-15 in the training process could become an effective way to assess the physical fitness of swimmers, predict their results at a distance of 100 meters and make the necessary adjustments to training plans. Methods and structure of the study. The study involved 30 qualified swimmers whose results in the 100-meter freestyle in a 25-meter pool corresponded to 800 or more points according to the World Aquatics Point Scoring 2024 rating system. Results and conclusions. The results of the analysis revealed a statistically significant positive relationship (r = 0.65, p < 0.001) between the time spent on the 15-meter segment after the turn and the total time of the 100-meter swim. This allows us to consider TT-15 as an easily applicable tool for tracking swimmers’ fitness levels, predicting competitive results, and optimizing the training process. TT-15 can be especially useful during the competitive period, when operational monitoring of physical condition and timely adaptation of the training program are crucial. However, the limitations of the study, such as the small sample size, lower relevance for long-distance swimmers, and the lack of research in the 50-meter pool, indicate the need for further research in this area.